Structure of mixed ombrophyllous forests with Araucaria angustifolia (Araucariaceae) under external stress in Southern Brazil - Vibrans, Alexander C.; Sevegnani, Lúcia; Uhlmann, Alexandre; Schorn, Lauri A.; Sobral, Marcos G.; de Gasper, André L.; Lingner, Débora V.; Brogni, Eduardo; Klemz, Guilherme; Godoy, Marcela B.; Verdi, Marcio (Revista de Biología Tropical, 2011)
--